1999
DOI: 10.1086/306689
|View full text |Cite
|
Sign up to set email alerts
|

Kuiper Widefield Infrared Camera Far‐Infrared Imaging of the Galactic Center: The Circumnuclear Disk Revealed

Abstract: We present images of the Galactic center in the dust continuum at 31.5 and 37.7 km obtained with the Kuiper WideÐeld Infrared Camera on the Kuiper Airborne Observatory. The raw images have a spatial resolution of and cover a region roughly 10@ (R.A.) by 24@ (decl.) in extent. Here we discuss the D8A .5 innermost (6.9 ] 9.1 pc) regions roughly centered on Sagittarius A*, where the high signal-to-2@ .8 ] 3@ .6 noise ratio permits image restoration to spatial resolution at 31.5 and 37.7 km, respectively. D3A .6È5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
78
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(94 citation statements)
references
References 36 publications
15
78
1
Order By: Relevance
“…By using their 63 μm [O i] data toward the northern peak together with previous 146 μm [O i] and 158 μm [C ii] data (from Genzel et al 1985;Poglitsch et al 1991) as input to model calculations of collisional excitation and radiative transport, Jackson et al (1993) estimated that neutral (presumably atomic) gas inside the central cavity has a temperature ≈(170 ± 70) K, a true hydrogen density ≈3 × 10 5 cm −3 , a space-averaged hydrogen density ≈1.6 × 10 3 cm −3 (beam-averaged hydrogen column density in a 55 beam divided by an assumed line-of-sight pathlength of 1 pc; note, however, that the value reported in their Table 2 is too low by a factor of 2) and a total hydrogen mass (associated with the Northern and Eastern Arms) ≈300 M . Latvakoski et al (1999) found that the three arms of the Minispiral seen in thermal radio continuum emission have counterparts in dust far-infrared continuum emission, which tend to lie ≈1 −3 farther from Sgr A * . This configuration, they explained, is consistent with the radio and far-infrared features being photo-ionized and photo-dissociated, respectively, by UV sources very close to Sgr A * .…”
Section: The Central Cavitymentioning
confidence: 96%
See 1 more Smart Citation
“…By using their 63 μm [O i] data toward the northern peak together with previous 146 μm [O i] and 158 μm [C ii] data (from Genzel et al 1985;Poglitsch et al 1991) as input to model calculations of collisional excitation and radiative transport, Jackson et al (1993) estimated that neutral (presumably atomic) gas inside the central cavity has a temperature ≈(170 ± 70) K, a true hydrogen density ≈3 × 10 5 cm −3 , a space-averaged hydrogen density ≈1.6 × 10 3 cm −3 (beam-averaged hydrogen column density in a 55 beam divided by an assumed line-of-sight pathlength of 1 pc; note, however, that the value reported in their Table 2 is too low by a factor of 2) and a total hydrogen mass (associated with the Northern and Eastern Arms) ≈300 M . Latvakoski et al (1999) found that the three arms of the Minispiral seen in thermal radio continuum emission have counterparts in dust far-infrared continuum emission, which tend to lie ≈1 −3 farther from Sgr A * . This configuration, they explained, is consistent with the radio and far-infrared features being photo-ionized and photo-dissociated, respectively, by UV sources very close to Sgr A * .…”
Section: The Central Cavitymentioning
confidence: 96%
“…On the other hand, little molecular gas seems to be present, except possibly for a hot and dense molecular component detected in NH 3 (6, 6) emission very near Sgr A * (Herrnstein & Ho 2002). The general lack of molecular gas can be understood if any initially molecular cloud inside the central cavity has been largely photo-dissociated by the intense ambient UV radiation (Jackson et al 1993;Latvakoski et al 1999;Shukla et al 2004).…”
Section: The Central Cavitymentioning
confidence: 99%
“…However, the assumption of virialization yields unplausible masses of several 10 3 M per clump and few 10 5 M for the whole CA. The masses of atomic hydrogen inside the cavity (dominated by the minispiral NA) range between 50 -300 M (from FIR and O i observations; Telesco et al 1996;Latvakoski et al 1999;Jackson et al 1993), while the molecular gas mass is most likely only a fraction of this.…”
Section: Origin Of the Molecular Gas In The Central 20 Arcsecondsmentioning
confidence: 99%
“…The inner edge of the CND in the southwest lobe appears to be tightly outlined by the western ionized arc. This correlation has led to the idea that the western arc might be the ionized boundary of the CND where the strong pervasive UV field from the central cluster is responsible for the heating of the CND Amo-Baladrón et al 2011) and the mini-spiral structure (Latvakoski et al 1999). This association was kinematically confirmed by Christopher et al (2005).…”
Section: Cnd Structure and Interaction With The Mini-spiralmentioning
confidence: 99%
“…Though this arm appears to be crossing the eastern extension of the CND, there is no evidence of perturbation of the molecular material, which indicates that both features are not in the same plane. Dust emission modeling (Latvakoski et al 1999) and H92α kinematics (Zhao et al 2009) showed that the eastern arm must be significantly inclined with respect to the eastern CND. Fig.…”
Section: Cnd Structure and Interaction With The Mini-spiralmentioning
confidence: 99%